Assessment of the Impact of Bidens pilosa on Behavioral, Oxidative Stress and Cerebellar Cortical Histoarchitectural Alterations During Bisphenol A Exposure in Mice - Jama IA; Usman IM; Oviosun A; Eze ED; Adeniyi IA; Etukudo EM; Kwizera E; Owembabazi E; Anyanwu E (Journal of Experimental Pharmacology, 2025)
Ishak Abdi Jama,1 Ibe Michael Usman,1 Augustine Oviosun,1 Ejike Daniel Eze,2 Ismahil Adekunle Adeniyi,3 Ekom Monday Etukudo,1 Eliah Kwizera,4 Elna Owembabazi,1 Emeka Anyanwu1 1Department of Anatomy, Faculty of Biomedical Sciences, Kampala International University, Western Campus, Bushenyi, Uganda; 2Department of Physiology, School of Medicine, Kabale University, Kabale, Uganda; 3Department of Physiology, Faculty of Biomedical Sciences, Kampala International University, Western Campus, Bushenyi, Uganda; 4Department of Biochemistry, Faculty of Biomedical Sciences, Kampala International University, Western Campus, Bushenyi, UgandaCorrespondence: Ibe Michael Usman, Email gopama13@gmail.comPurpose: The use of medicine plants in the management of various human ailments have gained lots of attention in recent time; hence, the present study aimed to investigate the impact of Bidens pilosa on the behavioral, oxidative stress and cerebellar cortical histoarchitectural alterations during bisphenol A exposure in mice.Methods: Thirty (30) adult male mice were divided into six groups. Group 1 received distilled water (2 mls/kg b.w). and group 2 was treated with (bisphenol A) BPA (100 mg/kg body weight). Groups 3– 5 were co-treated with varying doses of Bidens pilosa (250 mg/kg, 500 mg/kg, and 1000 mg/kg b.w). and group 6 received vitamin C (60 mg/kg b.w). along with BPA. The animals underwent neurobehavioral tests (beam walking and wire hang). Other parameters evaluated included body weight, oxidative stress biomarkers, and cerebellar histology.Results: Animals treated with high doses of Bidens pilosa spent less time crossing the beam during the beam walking test and more time in the wire hang test than those treated with BPA alone. Lowered malondialdehyde level and higher catalase and superoxide dismutase activity was observed in Bidens pilosa treated groups than in the BPA-only group. Histological examination revealed a significant improvement in the cerebellar tissue structure in Bidens pilosa treated groups, particularly at higher doses.Conclusion: Bidens pilosa demonstrated potential protective effects against BPA-induced oxidative stress and negative histological changes in the cerebellar cortex, suggesting its therapeutic potential for mitigating BPA neurotoxicity. Further research is needed to explore the therapeutic applicability.Keywords: cerebellar cortex, Bidens pilosa, bisphenol A, oxidative stress, neuroprotection